Can mutual fund stars really pick stocks? New evidence from a bootstrap analysis - Robert Kosowski; Allan Timmermann; Russ Wermers; Hal White (University of Cologne, Centre for Financial Research (CFR), 2005)
We apply a new bootstrap statistical technique to examine the performance of the U.S. openend, domestic-equity mutual fund industry over the 1975 to 2002 period. Specifically, we bootstrap the joint distribution of performance measures () across all funds to determine whether managers of high-alpha funds are simply the luckiest in a large field of managers, or whether they possess genuine stockpicking skills. This bootstrap approach is necessary because the cross-section of mutual fund alphas has a complex, non-normal distributiondue to heterogeneous risk-taking by funds as well as non-normalities in individual fund alpha distributions. Our bootstrap approach reveals findings that differ from many past studies. Specifically, we find that a sizable minority of managers really do pick stocks well enough to more than cover their costs. Moreover, our bootstrap indicates that the superior alphas of these managers persist.
Keywords: 330